2022
DOI: 10.1002/ecs2.4202
|View full text |Cite
|
Sign up to set email alerts
|

Parsing spatial and temporal variation in stream ecosystem functioning

Abstract: The decomposition of organic matter is a fundamental ecosystem-level process that governs nutrient cycling, fuels ecosystems, and impacts our global climate. Despite the central importance of this process for ecosystems across the planet, little is known about how the capacity of ecosystems to decompose organic matter-that is, their decomposition potential-varies across time and space. Closing this gap is needed to provide baseline information on the dynamics of ecosystems, for tracking anthropogenic impacts, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
(51 reference statements)
1
2
0
Order By: Relevance
“…Although we observed an ~117% increase in saltcedar decomposition and attribute this acceleration to interactions among warming, litter quality, and a high abundance of mudsnails, it is worth noting that the magnitude of this change is comparable to interannual variability of litter breakdown observed in other studies (Mancuso et al, 2022). For example, Mancuso et al studied OM decomposition in 26 streams throughout northern Michigan over nine consecutive years and found that the rate of cotton‐strip decomposition varied as much as 2000% (0.002–0.05 k ) within a single stream.…”
Section: Discussionsupporting
confidence: 85%
“…Although we observed an ~117% increase in saltcedar decomposition and attribute this acceleration to interactions among warming, litter quality, and a high abundance of mudsnails, it is worth noting that the magnitude of this change is comparable to interannual variability of litter breakdown observed in other studies (Mancuso et al, 2022). For example, Mancuso et al studied OM decomposition in 26 streams throughout northern Michigan over nine consecutive years and found that the rate of cotton‐strip decomposition varied as much as 2000% (0.002–0.05 k ) within a single stream.…”
Section: Discussionsupporting
confidence: 85%
“…Although the technical ability to measure ecosystem metabolism has greatly advanced in recent years (Ferreira et al, 2020), such monitoring remains limited, especially across large spatial scales, because it is difficult to ensure comparability of measurement techniques (Brosed et al, 2022). Additionally, interpretation of site-specific results in terms of ecosystem health remains challenging (Mejia et al, 2018) and high spatial variability between sampling sites makes it difficult to synthesize results from specific sites to entire watersheds (Mancuso et al, 2022). For this reason, we decided to seek an alternative approach to monitoring ecosystem function, and turned instead to reviewing studies that have shown strong statistical relationships between landscape composition and pattern and various ecological processes (Qiu and Turner, 2015;Duarte et al, 2018;Qiu, 2019;Metzger et al, 2021).…”
Section: Indicators Of Ecosystem Health For the Mississippi-atchafala...mentioning
confidence: 99%
“…On the other hand, highland grasslands often have natural open streams areas without riparian vegetation (Fernandes 2016). Therefore, understanding how spatial heterogeneity of gallery riparian zones act in highland grasslands stream systems is fundamental to understanding the dynamics and importance of leaf litter breakdown process and decomposer's community in ecosystems as a whole (Rezende et The rate of leaf litter breakdown and decomposer's community may changes from year to year in response to physical and chemical changes by environmental local alterations (Mancuso et al 2022). This temporal niche variability in local environmental characteristics may have a signi cant impact on the quantity and quality of leaf litter input (Peng et al 2018), affecting the decomposition process, and consequently, the availability of nutrients and aquatic biodiversity (Lodge and Cantrell 1995;Atkins et al 2017;Liu et al 2023).…”
Section: Introductionmentioning
confidence: 99%